Rheological behavior of high methoxyl pectin from the pulp of tamarillo fruit (Solanum betaceum) - Nascimento, Georgia Erdmann do; Simas-Tosin, Fernanda F.; Iacomini, Marcello; Gorin, Philip Albert James; Cordeiro, Lucimara M.C. (Carbohydrate polymers, 2016)
•Rheological behavior of a high methoxyl pectin from tamarillo pulp was studied.•STW-A dispersed in water (3–8% w/w) showed liquid-like behavior.•STW-A (2–3%), at pH 3 and with 50% sucrose showed shear-thinning flow and gel-like behaviors.•STW-A in the presence of sucrose did not follow the Cox and Merz rule.•STW-A (at 2 and 3%) with sucrose formed thermostable gels (at 5–80°C and 80–5°C). Rheological behavior of a high methyl-esterified pectic fraction (STW-A) from tamarillo was evaluated at different concentrations in water and with sucrose (50% w/w, pH 3). STW-A dispersions at 3, 5, and 8% (w/w) showed low apparent viscosities, shear-thinning and liquid-like behaviors. They were well fitted using the Ostwald–de Waele model and obey the Cox–Merz rule. The viscosity and the viscoelastic behavior were greatly modified by the presence of sucrose. STW-A at 1% (+ sucrose) showed shear-thinning and concentrated solution behavior. Pronounced shear-thinning and gel-like behaviors were obtained with STW-A at 2 and 3% (+ sucrose). Their flow curves profiles were better fitted using the Hershel–Bulkley model and not followed the Cox and Merz rule. Temperature sweeps (5–80°C) showed that STW-A formed thermostable gels. Altogether, our results suggested tamarillo can be a new source of pectin with potential applications as thickeners/gelling agents depending on solvent or applied processes.